RIVERFRONT CITY HOTEL DI SUNGAI SERANG WATES, KULON PROGO - , EKA KRISTALINA KURNIAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta as a city of students and cultures has its own magnet to attract people to come. DIY Provinceâs visitor number increases every year. Those visitors not only come for leisure activities but also for investment, convention and important meeting. It encourages the rapid rate of building hotel growth that is concentrated in the downtown Yogyakarta city. City hotel located in Kulon Progo is served to attract visitors to come. The existence of hotels outside Yogyakarta city can be another magnet so that the visitors dispersion in DIY Province can be spread more evenly. Based on case studies, a building can be a main attraction that revive the economy of a region. A riverside hotel is still infrequent especially a hotel that makes the river as the forefront. Riverfront concept applied by integrating between the hotel building with the river landscape as the appreciation to the river. Thus public awareness of the existence of river can be more recognized as a positive impact for the environment as well as the river itself.